1994
DOI: 10.1172/jci117144
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating activity of a Ca(2+)-sensitive K+ channel. A prerequisite for migration of transformed Madin-Darby canine kidney focus cells.

Abstract: Migration plays an important role in the formation of tumor metastases. Nonetheless, little is known about electrophysiological phenomena accompanying or underlying migration. Previously, we had shown that in migrating alkali-transformed Madin-Darby canine kidney focus (MDCK-F) cells a Ca+-sensitive 53-pS K+ channel underlies oscillations of the cell membrane potential. The present study defines the role this channel plays in migration of MDCK-F cells. We monitored migration of individual MDCK-F cells by video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 41 publications
4
82
0
1
Order By: Relevance
“…These fast-growing cells express Ca 2ϩ -activated K ϩ channels that largely enhance cell migration (23). The fastgrowing T 84 cells described in the present study showed a strong increase in the expression of the Best1 Cl Ϫ channel along with Eag1 potassium channels.…”
Section: Transformation Of Colonic Epithelial Cells Increases Prolifesupporting
confidence: 49%
“…These fast-growing cells express Ca 2ϩ -activated K ϩ channels that largely enhance cell migration (23). The fastgrowing T 84 cells described in the present study showed a strong increase in the expression of the Best1 Cl Ϫ channel along with Eag1 potassium channels.…”
Section: Transformation Of Colonic Epithelial Cells Increases Prolifesupporting
confidence: 49%
“…It is generally accepted that migrating cells are polarized along their axis of movement and establish an intracellular Ca 2+ gradient with a lower [Ca 2+ ] at the cell npg front [14][15][16]. By mediating salt efflux or influx, followed by osmotic water flow, ion channels and transporters play a pivotal role in regulating cell volume during migration.…”
Section: Mia Protein Secretion Is a Ca 2+ -Regulated Processmentioning
confidence: 99%
“…By mediating salt efflux or influx, followed by osmotic water flow, ion channels and transporters play a pivotal role in regulating cell volume during migration. These considerations apply in particular to the KCa3.1 channel, which is activated in migrating cells by increased Ca 2+ [16,37], especially at the cell rear [22]. Since KCa3.1 channel expression was observed in malignant melanoma cells [19], we decided to test for KCa3.1-mediated potassium currents in Mel Im cells and to investigate whether there is a direct association of channel activity and MIA protein secretion.…”
Section: Mia Protein Secretion Is a Ca 2+ -Regulated Processmentioning
confidence: 99%
See 2 more Smart Citations